2013
DOI: 10.1111/1755-0998.12152
|View full text |Cite
|
Sign up to set email alerts
|

Restriction site‐associated DNA sequencing generates high‐quality single nucleotide polymorphisms for assessing hybridization between bighead and silver carp in the United States and China

Abstract: Bighead carp (Hypophthalmichthys nobilis) and silver carp (H. molitrix) are invasive species and listed as US federally injurious species under the Lacy Act. They have established populations in much of the Mississippi River Basin (MRB; Mississippi, Illinois, and Missouri rivers) and are capable of producing fertile hybrids and complex introgression. Characterizing the composition of this admixture requires a large set of high-quality, evolutionarily conserved, diagnostic genetic markers to aid in the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…This method is popular and has been used in many studies since its inception (Figure S1). RAD sequencing has been used, particularly in fish, to identify population divergence (Boehm, Waldman, Robinson, & Hickerson, 2015; Ferchaud & Hansen, 2016; Larson et al., 2014), for SNP identification in polyploid fish (Hohenlohe, Amish, Catchen, Allendorf, & Luikart, 2011; Ogden et al., 2013; Palti et al., 2014), in phylogeographic studies (Macher et al., 2015; Reitzel, Herrera, Layden, Martindale, & Shank, 2013), for QTL analysis (Gagnaire, Normandeau, Pavey, & Bernatchez, 2013; Houston et al., 2012; Yoshizawa et al., 2015), for linkage mapping (Brieuc, Waters, Seeb, & Naish, 2014; Henning, Lee, Franchini, & Meyer, 2014), in hybridization studies (Hand et al., 2015; Lamer et al., 2014; Pujolar et al., 2014), for exploration of genome architecture and evolution (Brawand et al., 2014; Kai et al., 2014; Waples, Seeb, & Seeb, 2016), and in phylogenetic analyses (Gonen, Bishop, & Houston, 2015; Wagner et al., 2013). This methodology should be particularly suited to phylogeographic studies as the inference power from large numbers of markers may identify patterns that are not easily visible in traditional analyses based on relatively few loci (Davey et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This method is popular and has been used in many studies since its inception (Figure S1). RAD sequencing has been used, particularly in fish, to identify population divergence (Boehm, Waldman, Robinson, & Hickerson, 2015; Ferchaud & Hansen, 2016; Larson et al., 2014), for SNP identification in polyploid fish (Hohenlohe, Amish, Catchen, Allendorf, & Luikart, 2011; Ogden et al., 2013; Palti et al., 2014), in phylogeographic studies (Macher et al., 2015; Reitzel, Herrera, Layden, Martindale, & Shank, 2013), for QTL analysis (Gagnaire, Normandeau, Pavey, & Bernatchez, 2013; Houston et al., 2012; Yoshizawa et al., 2015), for linkage mapping (Brieuc, Waters, Seeb, & Naish, 2014; Henning, Lee, Franchini, & Meyer, 2014), in hybridization studies (Hand et al., 2015; Lamer et al., 2014; Pujolar et al., 2014), for exploration of genome architecture and evolution (Brawand et al., 2014; Kai et al., 2014; Waples, Seeb, & Seeb, 2016), and in phylogenetic analyses (Gonen, Bishop, & Houston, 2015; Wagner et al., 2013). This methodology should be particularly suited to phylogeographic studies as the inference power from large numbers of markers may identify patterns that are not easily visible in traditional analyses based on relatively few loci (Davey et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping analysis of 57 species‐specific SNPs developed by Lamer et al. (2014) identified B1 as a hybrid; however, transcriptomic data suggested B1 was a second‐generation backcross with bighead carp (Figure 3). A similar situation occurred between S1 (second‐generation backcross with silver carp) and S2 (pure silver carp), whose transcriptomic analysis suggests S1 should be a post‐first‐generation backcross with silver carp.…”
Section: Resultsmentioning
confidence: 99%
“…Within the native ranges, reproduction isolation may be maintained by spatial or temporal isolation rather than pre‐ or postzygotic barriers (Mayr, 1970). This study provides an insight into hybridization and introgression of bigheaded carps, which supports the prediction that bigheaded carps in the MRB are likely to form a hybrid swarm (Lamer et al., 2014). This introgressive hybridization may result from a shift to a more homogenous reproductive environment in the MRB which lacks extrinsic factors that are required for the restriction of gene flow between species (Seehausen, Takimoto, Roy, & Jokela, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…ability to obtain prey or avoid predation). Thus, quantifying nutritional status can provide insights into hybrid performance relative to their parents and may provide critical information for invasive species that hybridize, such as bighead carp, Hypophthalmichthys nobilis, and silver carp, Hypophthalmichthys molitrix (hereafter, bigheaded carps; Lamer et al 2010Lamer et al , 2014Lamer et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that bigheaded carps may negatively affect invaded habitats (Irons et al 2007;Sass et al 2010;Calkins et al 2012;Sass et al 2014). Bigheaded carps have hybridized in native and non-native habitats, with an estimated 44% of individuals in the MRB existing as hybrids (Lamer et al 2010(Lamer et al , 2014(Lamer et al , 2015. Physiological performance of hybrids relative to their parents is unknown, and quantifying differences could have significant implications for better understanding and managing these invaders.…”
Section: Introductionmentioning
confidence: 99%